Relationship between the range of motion and isometric strength of elbow and shoulder joints and ball velocity in women team handball players - Schwesig, R.; Hermassi, S.; Wagner, H.; Fischer, D.; Fieseler, G.; Molitor, T.; Delank, K. S. (The Journal of Strength and Conditioning Research, 2016)
The aims of this study were to investigate relationships between isometric strength and range of motion (ROM) of shoulder and elbow joints and compare 2 different team handball throwing techniques in women team handball. Twenty highly experienced women team handball players (age: 20.7 ± 2.9 years; body mass: 68.4 ± 6.0 kg; and height: 1.74 ± 0.06 m) participated in this study. The isometric strength (hand-held dynamometer) and ROM (goniometer) of shoulder and elbow joints were measured at the beginning of the preseasonal training. After clinical examination, the subjects performed 3 standing throws with run-up (10 m) and 3 jump throws over a hurdle (0.20 m). The mean ball velocity was calculated from 3 attempts and measured using a radar gun. The results showed that the ball velocity of the standing throw with run-up (vST) was significantly higher than that of the jump throw (vJT) (25.5 ± 1.56 vs. 23.2 ± 1.31 m/s; p < 0.001). Therefore, significant playing position effects (p = 0.021) were only found for ST. Goalkeepers (n = 2) had the lowest (22.6 ± 0.04 m/s) and backcourt players (n = 9), the highest (26.1 ± 1.36 m/s) vST. The retroversion strength in the shoulder was the only parameter with relevant correlations to both throws (vST: r = 0.52, and vJT: r = 0.43). Other relevant relationships to vJT were found for adduction strength shoulder (r = 0.55) and ROM flexion elbow (r = -0.54). The vST was only correlated to the glenohumeral internal rotation deficit. As a consequence, strength is more important than the ROM, and in addition to this, the shoulder, compared with the elbow, has a greater influence on the vST in highly experienced women team handball players.